Optimization of Supercritical CO2 Extraction of Moringa oleifera Seed Oil Using Response Surface Methodological Approach and Its Antioxidant Activity - Chen, Xuexiang; Li, Zhuobin; Smith, Sarah A.; Chen, Mingxiu; Liu, Hanbin; Zhang, Jing; Tang, Lirong; Li, Jie; Liu, Qishan; Wu, Xian (Frontiers in Nutrition, 2022)
Moringa (Moringa oleifera) seed oil is an edible vegetable oil rich in unsaturated fatty acids. In this study, the supercritical CO2 fluid extraction method was employed to obtain the maximum yield of moringa seed oil. The effects of temperature, time, and pressure, three characteristics of extractions, on the extraction rate of Moringa seed oil were investigated by single factor test and response surface methodological approach. The optimal process conditions of supercritical CO2 fluid extraction of moringa seed oil were determined as extraction temperature of 45 °C, extraction time of 2.5 h, extraction pressure of 50 MPa, and CO2 flow rate of 240 L/h, resulting in a maximum yield of 38.54%. Composition analysis shows that the extracted moringa seed oil is rich in unsaturated fatty acids, including oleic acid, octadecanoic acid, palmitic acid, stearic acid, eicosanoic acid, etc. Furthermore, we found that Moringa seed oil exerted potent antioxidant activities on DPPH and hydroxyl radicals, and its efficacy was comparable to commercial peanut oil and tea oil. Overall, this novel extraction method of moringa seed oil may increase its potential value and application in the food and nutraceutical industries.